2002
DOI: 10.1083/jcb.200108089
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-specific RING finger-1 interacts with titin to regulate sarcomeric M-line and thick filament structure and may have nuclear functions via its interaction with glucocorticoid modulatory element binding protein-1

Abstract: The COOH-terminal A168–170 region of the giant sarcomeric protein titin interacts with muscle-specific RING finger-1 (MURF-1). To investigate the functional significance of this interaction, we expressed green fluorescent protein fusion constructs encoding defined fragments of titin's M-line region and MURF-1 in cardiac myocytes. Upon expression of MURF-1 or its central region (containing its titin-binding site), the integrity of titin's M-line region was dramatically disrupted. Disruption of titin's M-line re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
188
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(209 citation statements)
references
References 56 publications
17
188
1
3
Order By: Relevance
“…Interaction of titin with MuRF1 in sarcomeres has previously been reported (13,18). Our data and that of other groups indicate that MuRF1 exists in multiple locations within the cell, including the cytosol, along the sarcomere, and within the nucleus.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Interaction of titin with MuRF1 in sarcomeres has previously been reported (13,18). Our data and that of other groups indicate that MuRF1 exists in multiple locations within the cell, including the cytosol, along the sarcomere, and within the nucleus.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have shown that MuRF1 is found in several niches within myocytes: the cytosol, nucleus, and along myofibrils (13,18). We also observed similar localization of MuRF1 in cardiomyocytes treated with or without PE (Fig.…”
Section: Murf1supporting
confidence: 86%
See 1 more Smart Citation
“…46 MuRF-1 binds the giant sarcomeric protein titin, suggesting that MuRF-1 regulates the stability of the large structural protein. 47 In addition, Cohen et al 48 reported that MuRF-1 ubiquitinates MyBP-C, MyLC1, and MyLC2, including in myofibrils. Because these proteins stabilize the thick filament, their selective ubiquitination may facilitate thick filament disassembly.…”
Section: Discussionmentioning
confidence: 99%
“…These two genes correspond to ubiquitinprotein ligases expressed solely in skeletal and cardiac muscle that mediate the processes of muscle remodeling and increase proteolysis of disuse atrophy. For instance, MURF1 was firstly identified as the ubiquitin-ligase responsible for the direct binding and degradation of titin, a huge myofibrillar protein, and myosin heavy chain (McElhinny et al 2002;Clarke et al 2007). Further confirm of the functional role of these atrogenes came from the experiments performed on MAFbx-/-and MURF1-/-transgenic mice, refractory to muscle-loss phenomena induced by denervation.…”
Section: Atrophy and Atrogenesmentioning
confidence: 99%